Biotratamento de sacolas plásticas de supermercado - Passolongo, Fernanda Heloisa [UNESP] (Universidade Estadual Paulista (Unesp), 2009)
Supermarket plastic bags are produced by high density polyethylene (HDPE) and low density polyethylene (LDPE) resins. In Brazil, are produced annually around 150 plastic bags per capita. Disposed in landfills, the supermarket plastic bags prevent the passage of water by slowing the breakdown of biodegradable materials and hindering compaction of waste, according to their low degradability. This work investigated the biodegradation of PE bags containing additive oxo-biodegradable and bags without additives: buried in soil columns, exposed in a controlled environment and exposed to air. The analysis methods used to assess the changes brought in the bags with respect to microbial action and exposure time were weight loss, thickness measurement, infrared (FTIR), scanning electron microscopy (SEM) and contact angle. The results showed that the use of prodegradant agents such as oxobiodegradable additives in polyethylene bags, buried in soil for 270 days, was not efficient to accelerate the biodegradation by microorganisms. It seems that these additives have been more efficient to degrade the colored pigmentation of printed bags, under the influence of light and heat.

As sacolas de supermercado são produzidas a partir de resinas de polietileno de alta densidade (PEAD) e polietileno de baixa densidade (PEBD). No Brasil, são produzidas anualmente cerca de 150 sacolas plásticas por habitante. Dispostas em aterros sanitários, as sacolas plásticas impedem a passagem de água retardando a decomposição dos materiais biodegradáveis e dificultando a compactação dos detritos, em função da sua baixa degradabilidade. Este trabalho investigou a biodegradação de sacolas de PE contendo aditivo oxi-degradável e sacolas não aditivadas, enterradas em colunas de solo, expostas em ambiente controlado e expostas ao ar livre. Os métodos de análise utilizados para avaliar as mudanças provocadas nas sacolas com relação a ação microbiana e o tempo de exposição, foram: perda de massa, medidas de espessura, infravermelho (FTIR), microscopia eletrônica de varredura (MEV) e ângulo de contato. Os resultados mostraram que a utilização de agentes pródegradantes, como os aditivos oxi-degradáveis em sacolas de polietileno enterradas em solos, durante 270 dias, não foi eficiente para acelerar a biodegradação por microrganismos. Parece que estes aditivos foram mais eficientes para degradar os pigmentos coloridos das sacolas impressas, sob influência de luz e calor.
Keywords: Resíduos; Biodegradação; Impacto ambiental; Pigmentos; Polimeros; Aditivos oxibiodegradáveis; Agentes pró-degradantes; Polymers; High density polyethylene; Prodegradant agents; Oxo-biodegradable additives